The multifaceted roles of BAF60 subunits in muscle: regulation of differentiation, reprogramming, and metabolic homeostasis - Liu, Yaoxia; Fan, Zhen; Zhai, Yang; Huang, Haotian; Shi, Ruifeng; Wang, Tao (Frontiers in Cell and Developmental Biology, 2025)
Muscle development and metabolic homeostasis are critical aspects of human health. As a key component of the SWI/SNF chromatin remodeling complex, the BAF60 subunit plays a widespread and crucial role in the differentiation, reprogramming, and metabolic regulation of skeletal, cardiac, and smooth muscle. Recent studies reveal that BAF60c promotes skeletal muscle differentiation and regeneration by interacting with MyoD, while also driving cardiac-specific gene expression and cooperating with transcription factors such as NKX2.5 and GATA Binding Protein 4 (GATA4) during heart development and remodeling. In smooth muscle, BAF60c interacts with serum response factor to maintain contractility and homeostasis by reducing inflammation and apoptosis. In contrast, BAF60a promotes inflammatory responses and extracellular matrix degradation, contributing to vascular diseases such as abdominal aortic aneurysm and atherosclerosis. Importantly, different BAF60 isoforms exhibit antagonistic, synergistic, or mutually exclusive effects in different muscle types, highlighting their complexity. This review provides a comprehensive overview of BAF60 isoforms’ regulatory roles, with an emphasis on their potential as therapeutic targets for muscle-related metabolic and vascular diseases.